STUDI SOSIAL EKONOMI PENGGUNAAN LABAN HUTAN KONVERSI UNTUK TRANSMIGRASI DI KALIMANTAN SELATAN - Ismatul Hakim (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
The transfer of convertion forest lands into transmigration areas must be geared towards improving and developing land productivity in order to obtain optimun socio-economic role of the rasources for the transmigrant and sustainability of agricultural production. In this rasearch respondent samples are purposively taken from the villages of Ambawang (15 families) as a less successful transmigration area and of Domit (115 familia) as a successful area. Both are located in Jorong sub-district, Tanah laut District, South Kalimantan.The resulis showed thet the per capita income of respondent family in Damit village is higher than that in Ambawang village (almost twice) and land productivity in Damit village is even 3 limes as in much as in .Ambawang village These mean that transmigration program in Damit village is more succasful than in Ambawang village. Land utilization in Damit and Ambowang villages is as foUows : I t e ms Precentage of land us Damit Ambawang.Rice field 181,80 125,71Home garden 104,17 82,76Farm land 26,57 34,57This can be interpreled that more land in Damit is suitable for rice field. Land use in transmigration areas depends on the suitability level of land for agricultaral extensification, the availability of water for irrigation, and background experience background of transmigration family.An average number of mandays per family per year is 2140.49 mandays which consists of: farming, rice field woking, off- farming and home gardening are 36.77%, 24.16%, 21.52%, and 16.60%, respectively. The total income per family both villages is Rp 1,275,086.300The saving level per family in Domit is Rp 333,794.20 and in Ambowang is Rp 541,303.00 but the Gross Domestic Product (PlJB) in Damit is Rp 873,075.00 and PDB in Ambawang is Rp 265,431.50. These mean that the equalization level of income distribution and the occess of transmigration community to the village development are better in Damit than on .Ambawang.In general, it can be concluded that practicing transmigration program by using convertion forest land in Jorong, South Kalima.tan can improve land productivity and socio-economic status of the tronsmigrants which makes them enjoying beller life in the new areas. The in depth study on socio-economic aspeci of transmigration is required by comparing their socio-economic status in their new area to their previous ones in Java.